If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 * 3x + -2 = 14 Multiply 2 * 3 6x + -2 = 14 Reorder the terms: -2 + 6x = 14 Solving -2 + 6x = 14 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + 6x = 14 + 2 Combine like terms: -2 + 2 = 0 0 + 6x = 14 + 2 6x = 14 + 2 Combine like terms: 14 + 2 = 16 6x = 16 Divide each side by '6'. x = 2.666666667 Simplifying x = 2.666666667
| x^2+22x-480=0 | | 1/4x-11 | | 32a-16=4a | | 4-b=1/3(2b+7) | | 15-(5/2)x=9+(1/2)x | | -50=2(v-4) | | 5k-30=3k+15 | | 6+(13-1)/4+2 | | -4y=2x | | 20-4x-2x+6-12x+6=4 | | 4x+7=-4+2x+25 | | 5x+3x=120 | | 0.55x+0.4x=x-2.5 | | 7x+52=2x+12 | | x/8=9/4.5 | | (5t+7)-(2t+7)= | | 12/(x^2+x-2)-(x+3)/(x-1)=(1-x)/(x+2) | | -3=-.5(n-6) | | -(1+7x)-6(-7x-x)=36 | | -5v-6(3v+2)=-150 | | 6v^2+13-28=0 | | 1/6(x+3)=1/9(8-x) | | -6y+17=3y-0 | | (2-x)/(x+2)+3=4/(x+2) | | 4x+(9-6(2x+3))-10= | | 15+w/9=-10 | | 6y^2+13y+15=0 | | 1/3x*(-18) | | 3z(z+6)=3z+18z-4 | | -5(8-4r)=-200 | | 0.2x+4.4=0.1x+3.1 | | 4/9w=88 |